Association Between 3 IL-10 Gene Polymorphisms and Cardiovascular Disease Risk: Systematic Review With Meta-Analysis and Trial Sequential Analysis. Issue 6 (February 2016) - Xuan, Yang; Wang, Lina; Zhi, Hong; Li, Xiaoshan; Wei, Pingmin
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Previous studies have yielded controversial results related to the contribution of interleukin 10 ( IL-10 ) gene polymorphisms ( IL-10 -592C/A, IL-10 -1082G/A, and IL-10 - 819C/T) in the progression of cardiovascular disease (CVD). Thus, we performed a meta-analysis to summarize this situation. Eligible studies were retrieved by searching PubMed, Embase, Web of Science, and Cochrane Library with the last search up to July 7, 2015. Data were pooled by odds ratios (ORs) and their 95% confidence intervals (CIs). False-positive report probability (FPRP) analysis was conducted for all significant findings. Genotype-based mRNA expression analysis was also performed using data from 270 individuals with different ethnicities. Finally, 19 studies for IL-10 -592C/A polymorphism (7284 cases and 7469 controls), 21 studies for IL-10 -1082G/A polymorphism (8263 cases and 5765 controls), and 12 studies for IL-10 -819C/T polymorphism (4502 cases and 3190 controls) were included in the meta-analyses. With respect to IL-10 -819C/T polymorphism, statistically significant decreased CVD risk was found when all studies were pooled into the meta-analysis (T vs C: OR   =   0.91, 95% CI   =   0.84–0.98; TT   +   TC vs CC: OR = 0.90, 95% CI = 0.81–1.00). Subgroup analyses stratified by disease subtype suggested the -819C/T polymorphism was significantly associated with a decreased CAD risk (T vs C: OR = 0.90, 95% CI = 0.83–0.97; TT vs CC: OR = 0.81, 95% CI = 0.66–1.00; TT vs TC   +   CC: OR = 0.82, 95% CI = 0.69–0.98; TT   +   TC vs CC: OR = 0.89, 95% CI = 0.80–0.99), which was noteworthy finding as evaluated by FPRP. However, with regard to IL-10 -592C/A and IL-10 -1082G/A polymorphisms, no significant association with CVD risk was observed in the overall and subgroup analyses. In conventional meta-analyses, the results suggested that IL-10 -819C/T polymorphism was associated with decreased risk of CVD, especially CAD outcome, whereas IL-10 -592C/A and IL-10 -1082G/A polymorphisms might have no influence on the susceptibility of CVD. However, trial sequential analysis does not allow us to draw any solid conclusion for the association between IL-10 -592C/A or IL-10 -1082G/A polymorphism and CVD risk. Further large and well-designed studies are still needed.